Analysis of Balje diagrams for a Wankel expander prototype. (15th March 2019) - Francesconi, Marco; Dori, Edoardo; Antonelli, Marco
Highlights: A Wankel expander was analyzed in the Balje chart. The device appeared as a middle-option between turbines and piston machines. The effects due to geometrical variations of the prototype were investigated. The influence of the working fluid was also considered. The results were provided by a numerical model experimentally validated. Abstract: Micro-generation thermal power plants are often equipped with volumetric expanders due to the possibility of efficiently use small volumetric flow rates. The choice between the use of one or another type of machine (Scroll, Screw, turbodynamic etc.) is usually performed on the basis of non-dimensional diagrams, such as the Balje diagram. Several types of small-size expanders have already been located on the Balje diagram, while others not, because they still are in their prototypical phase, and one of these is the Wankel expander. To the authors' knowledge, this paper is the first to analyze the position of this type of expander on the Balje diagram, as a function of the geometrical parameters of the operating chamber (primitive radius, eccentricity and axial depth) and the working fluid. The study was carried out by using a numerical model which has been previously validated by the comparison with experimental data. The results indicated that the Wankel expander can be located on a part of the Balje diagram which was not already covered by other known types of volumetric machine and exhibits a comparable efficiency. This remains true for a great extent of working conditions, sizes and working fluids. The influence of the geometrical aspect ratios of the chamber as well as of the working fluid was also analyzed.